2003
DOI: 10.1038/sj.ijo.0802541
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous adipose tissue blood flow varies between superior and inferior levels of the anterior abdominal wall

Abstract: OBJECTIVE: Blood flow regulation is thought to mediate the metabolic functions of adipose tissue. Different depots, and even different layers within the subcutaneous adipose tissue, may vary in metabolic activity and blood flow. Therefore, we investigated if any differences in subcutaneous adipose tissue blood flow (ATBF) exist at different locations of the anterior abdominal wall. METHODS: ATBF was measured 8-10 cm above or below the umbilicus, at 8-10 cm (both sides) from the midline, in 18 healthy subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…This substance determines the absolute level of ATBF, but a major proportion of the postprandial enhancement of ATBF is under ␤-adrenergic control (37). This means that NO has a permissive effect for other blood flow regulatory systems to exercise their effects, similar to what has been observed in pancreatic islets (38).…”
Section: Discussionsupporting
confidence: 51%
“…This substance determines the absolute level of ATBF, but a major proportion of the postprandial enhancement of ATBF is under ␤-adrenergic control (37). This means that NO has a permissive effect for other blood flow regulatory systems to exercise their effects, similar to what has been observed in pancreatic islets (38).…”
Section: Discussionsupporting
confidence: 51%
“…We and others have demonstrated previously that glucose ingestion increases ATBF in lean but not obese insulin resistant individuals. 17,18,22 Fasting ATBF was significantly higher in lean compared with obese subjects (2.5Ϯ0.5 versus 1.4Ϯ0.2 mL ⅐ 100 g tissue Ϫ1 ⅐ min Ϫ1 , respectively; Pϭ0.029). As anticipated, ATBF was markedly increased after ingestion of the glucose drink in lean subjects (baseline: 2.5Ϯ0.5 versus postprandial: 4.6Ϯ1.1 mL ⅐ 100 g tissue Ϫ1 ⅐ min Ϫ1 ; Pϭ0.027), but the postprandial increase in ATBF was completely blunted in obese subjects (baseline: 1.4Ϯ0.2 versus postprandial: 1.7Ϯ0.1 mL ⅐ 100 g tissue Ϫ1 ⅐ min Ϫ1 ; Pϭ0.146) (Figure 2A).…”
Section: In Obese Subjectsmentioning
confidence: 99%
“…19,26 The reason for this is that we and others have shown that ATBF is greater at the upper compared with the lower level of the abdomen, but is not different between the right and left sides at either level. 17,18 Postprandial measurements were not available for 2 lean subjects because of technical problems.…”
Section: Physiological Manipulation Of Adipose Tissue Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Blood perfusion in adipose tissue is more heterogeneous and differs from the corresponding cutaneous regions of the human body. 9,10 The deep and superficial fat layers are supplied more richly with vessels with a large diameter, whereas the intermediate fat layer is supplied with terminal branches of these vessels. 11 In current clinical practice, the inferior, rather than the superior, epigastric pedicle is crucial when lower abdominal tissue is transposed for purposes of autologous breast reconstruction.…”
mentioning
confidence: 99%